1895 Or.§Laws 95, An Act for the Protection of Game, Fish and Wild Fowl of the State of Oregon, and to Provide for the Appointment of§a Fish and Game Warden, § 16. - (:unkn) unknown (My University, 1895)
Every person who shall use any batteries or swivel or pivot-gun, or any other gun than one to be held in the hands and fired from the shoulder, either from the shore or on a boat, raft or other device, on the Columbia river, or on any other lake or river in the state of Oregon, at any time, for the purpose of shooting wild ducks, geese, swan or other water fowl, shall be guilty of a misdemeanor, and upon conviction thereof, shall be punished as hereinafter provided.
Keywords: HUNTING REGULATION